Tradition in the architectural thought of Julio Cano Lasso. Tradition as a system - Martín Robles, Inés; Pancorbo Crespo, Luis (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
We start from the idea that the focus on architecture and the thought of Julio Cano Lasso is the mode of transmission and survival of the past in the present, ie; the tradition. This research adopts in Cano a dual form. On one hand, the tradition considered as a continuous flow, maintaining constant structural characteristics and subjected to a selection process immanent that discards what is superfluous and distills only what is valuable. This theoretical statement results in the use of typology as a design method. On the other hand, ,there is tradition inserted into the fractional temporality of personal memory that destroys history as continuity and as immanence, and moves away from the evolutionism and the teleological claims of the previous statement. The latter is revealed in his work by using the reference method. In this paper we deal with analyzing the architect thinking regarding the first conceptual line. We review the writings of Cano and, through the comparison with their documented sources, Ortega y Gasset and Pedro Salinas, and the writings of other authors such as Aldo van Eyck, Igor Stravinsky, Alasdair MacIntyre, T.S. Eliot or Eugenio Trías, we will try to clarify the meaning of tradition as system for the architect, along with other related concepts: art, history, evolution, progress, modernity, originality and eclecticism.
Keywords: Julio Cano Lasso; tradition; modernity; originality; technique; history